Public Education Expenditure and Economic Growth: an Econometric Analysis - Subhasmita Rana (HM Journals, 2022)
The study shows the dynamics of expenditure on education and economic growth in all the major Indian states both in the short run and long run though our study that satisfies the long run association by Johansen cointegration. The study is used panel data from 1990 to 2022. The panel error correction supports the long-term Granger causality between expenditure on education and economic growth in all the states. Here the value is negative and significant and the coefficient 0.731 is showing the speed of adjustment towards equilibrium. So, we can state the speed is 7.31% per year adjustment towards equilibrium. However, there is no short-run Granger causality witnessed from educational expenditure to economic growth. It is evident that only in long-run educational expenditure has a significant impact on economic growth. In the short term, expenditure on education does not Granger cause economic growth. Therefore, the study confirms that in short run expenditure on education does not cause economic growth while in the long term it causes economic growth in the major Indian states.